2012
DOI: 10.1080/19768354.2012.696554
|View full text |Cite
|
Sign up to set email alerts
|

Various pain stimulations cause an increase of the blood glucose level

Abstract: The relationship between pain stimulation and the blood glucose level was studied in ICR mice. We examined the possible change of the blood glucose level after the pain stimulation induced by acetic acid injected intraperitoneally (i.p.),, formalin injected subcutaneously (s.c.) into the hind paw, or substance P (SP), glutamate, and proinflammatory cytokines (TNF-a and IFN-g) injected intrathecally (i.t.). We found in the present study that acetic acid, formalin, SP, TNF-a, and IFN-g increased the blood glucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…Our result is in line with the previous studies which show D-glucose feeding increases the blood glucose level [9,14]. Although supraspinal treatment with CTX alone does not affect the blood glucose level (Fig.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Our result is in line with the previous studies which show D-glucose feeding increases the blood glucose level [9,14]. Although supraspinal treatment with CTX alone does not affect the blood glucose level (Fig.…”
Section: Discussionsupporting
confidence: 94%
“…We recently found that the blood glucose level is elevated in acetic acid-induced writhing pain animal model as well as formalin pain model [9]. Furthermore, we recently found that pain stimulation induced by proinflammatory cytokines such as TNF-α (tumor necrosis factor-α), IFN-γ (interferon-γ) and IL-1β (inetrleukin1β) administered spinally, also causes an elevation of the blood glucose level [9,14]. Similar to the results found in D-glucose fed animal model, we found in the present study that supraspina pretreatment with CTX further enhances the blood glucose level induced by formalin-induced pain stimulation (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in an earlier clinical study, Sala et al [47] reported that a lower dose of insulin is used to regulate the BGL in patients with spinal cord injury. In addition, we recently found that substance P or several proinflammatory cytokines such as TNF-α, IFN-γ and IL-1β administered spinally cause an elevation of the BGL [48,49]. Taken together from the results of our present study and other groups, more pharmacological studies on the role of the spinal cord in the regulation of the BGL should be performed in the future.…”
Section: Discussionmentioning
confidence: 88%
“…In an earlier clinical study, Sala et al (1999) have reported that less dose of insulin is used to regulate the blood glucose level in patients with spinal cord injury. In addition, we recently found that substance P or several pro-inflammatory cytokines, such as TNF-α, IFN-γ and IL-1β administered spinally causes an elevation of the blood glucose level (Sim et al, 2012a(Sim et al, , 2012b. Furthermore, our recent study has also reported that GABA receptor agonists administered spinally cause the elevation of the blood glucose level (Sim et al, 2013).…”
Section: Discussionmentioning
confidence: 90%